2020
DOI: 10.1038/s41598-020-76008-2
|View full text |Cite
|
Sign up to set email alerts
|

A single bout of downhill running attenuates subsequent level running-induced fatigue

Abstract: Fatigue can be defined as exercise-induced strength loss. During running, fatigue can be partially explained by repetitive low-intensity eccentric contractions-induced muscle damage (EIMD). Previous studies showed that a bout of downhill running (DR) attenuated subsequent EIMD. Thus, we tested if a 30-min DR bout would attenuate fatigue induced by subsequent 60-min level running (LR). Twenty-seven male college students were randomly allocated to an experimental (EXP) or a control (CON) group. All participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 40 publications
(76 reference statements)
3
10
0
Order By: Relevance
“…The changes in neuromuscular function (i.e., IPT, RTD, and CMJ/SJ heights) and indirect markers of EIMD (i.e., muscle soreness, CIR, ROM, and serum CK activity) following downhill running observed in the current study corroborated to what has been reported in the literature ( Chen et al, 2007 , 2009 ; Assumpção et al, 2020 ; Lima et al, 2020 ). The obtained data confirmed that the explosive strength—assessed as RTD and jump height—was compromised immediately following downhill running but recovered 3–4 days after it while maximal strength—assessed as IPT—remained compromised until at least 4 days post-downhill running.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The changes in neuromuscular function (i.e., IPT, RTD, and CMJ/SJ heights) and indirect markers of EIMD (i.e., muscle soreness, CIR, ROM, and serum CK activity) following downhill running observed in the current study corroborated to what has been reported in the literature ( Chen et al, 2007 , 2009 ; Assumpção et al, 2020 ; Lima et al, 2020 ). The obtained data confirmed that the explosive strength—assessed as RTD and jump height—was compromised immediately following downhill running but recovered 3–4 days after it while maximal strength—assessed as IPT—remained compromised until at least 4 days post-downhill running.…”
Section: Discussionsupporting
confidence: 91%
“…The first experimental session consisted of performing the baseline measurements of all the dependent variables followed by a 30-min downhill run at a treadmill (Pulsar, h/p/Cosmos, Germany) with a slope of − 15% and at a speed equivalent to 70% of individual vVO 2 max. These downhill running settings are shown to induce significant muscle damage by our group ( Lima et al, 2018 , 2019 , 2020 ; Assumpção et al, 2020 ) and another independent research group ( Chen et al, 2007 , 2009 ). The dependent variables measurements were repeated for 15 min following downhill running except for indirect markers of EIMD.…”
Section: Methodsmentioning
confidence: 62%
“…The changes in neuromuscular function (i.e., IPT, RTD, and CMJ/SJ heights) and indirect markers of EIMD (i.e., muscle soreness, CIR, ROM, and serum CK activity) following downhill running observed in the current study corroborated to what has been reported in the literature (Chen et al, 2007(Chen et al, , 2009Assumpção et al, 2020;Lima et al, 2020). The obtained data confirmed that the explosive strength-assessed as RTD and jump height-was compromised immediately following downhill running but recovered 3-4 days after it while maximal strength-assessed as IPT-remained compromised until at least 4 days post-downhill running.…”
Section: Susceptibility To Exercise-induced Muscle Damagesupporting
confidence: 90%
“…The first experimental session consisted of performing the baseline measurements of all the dependent variables followed by a 30min downhill run at a treadmill (Pulsar, h/p/Cosmos, Germany) with a slope of − 15% and at a speed equivalent to 70% of individual vVO 2 max. These downhill running settings are shown to induce significant muscle damage by our group (Lima et al, 2018(Lima et al, , 2019(Lima et al, , 2020Assumpção et al, 2020) and another independent research group (Chen et al, 2007(Chen et al, , 2009. The dependent variables measurements were repeated for 15 min following downhill running except for indirect markers of EIMD.…”
Section: Methodsmentioning
confidence: 99%
“…However, there are also studies that have reported no differences in muscle performance measures (26,40,49), running economy (24), and running time-to-exhaustion (23) between 2 bouts of multiarticular muscle-damaging exercises. In addition, for studies that reported lower levels of CK and DOMS after the second bout of running activities (3,9,26,28,44–46,49–51,54,56), the magnitude of changes varied substantially between studies, making overall interpretations difficult. Collectively, the magnitude of the RBE trend seems to be influenced by several methodological factors.…”
Section: Introductionmentioning
confidence: 99%